THE CONCEPT OF NAFS IN THE NAQSHBANDIYA DOCTRINE - Navruzova Gulchekhra Nematovna (Scholar Express Journal, 2023)
The article presents a philosophical analysis of the concept of nafs in the world-famous Naqshbandiya doctrine, founded by Muhammad ibn Muhammad al-Bukhari (1318-1389), known as Bahauddin Naqshband. Comparative analysis of Naqshband's ideas about nafs in the work "Makomati Khoja Bahauddin Naqshband", Khoja Yusuf Hamadani in the work "Okobi tarkat" about riezati nafs. Based on the sources, the question of nafs, its seven types, nafsi ammor and its upbringing is philosophically analyzed
Keywords: Bahauddin Naqshband; Naqshbandiya; Yusuf Hamadoni